Administrative Professional: theories and procedures - Fulton-Calkins, Patsy; Stulz, Karin M. (Singapore, 2010)
The book equips the readers to handle whatever workplace challenges may come the way by providing instruction and activities directed toward technology, communication, and human relations.
Keywords: Office practice